SOCIAL CONFLICT MANAGEMENT TRAINING FOR RESIDENTS OF PAROPO-RAMA SETTLEMENT, MAKASSAR CITY - Ichlas Afandi; Musyarani Usman; Rudy Yusuf; mayenrisari Arifin; Andi Tenri Pada Rustham; Syurawasti Muhiddin (Universitas Negeri Surabaya, 2023)
After the conflict between the residents of Paropo village and Rama village in 2017, the fears of the two villagers that a similar conflict would still exist. Even though in practice, the recurrence of conflicts did not occur, feelings of worry often arose among the two villagers, especially the village officials (heads of the RT and RW of the two villages). They have made various efforts to overcome these concerns, such as increasing citizen alertness, limiting curfews, and strengthening coordination between government officials. But they feel that it is still not enough. Therefore, what is then considered important to do is to equip them with the ability to manage social conflict between residents. Of course conflict between residents is something that is not expected, but if it occurs, with the provision of conflict management skills, then if the conflict that arises can be resolved immediately, so that it does not have a negative impact that is detrimental to the sustainability of the social life of the people of Paropo village and Rama village.